Pengaruh Pengaruh Inflasi dan Tingkat Pengangguran Terbuka terhadap Ketimpangan Pendapatan di Provinsi Riau - Aryendi, Bani; Yulyanti, Sinta (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Income inequality is one of the factors influencing the economy of a region. The aim of this research is to examine the effect of inflation and open unemployment rate variables on income inequality. This research utilizies secondary data from the Central Statistics Agency (BPS) of Riau Province from 2014 to 2023. The research uses multiple linear regression methods. We use a quantitative approach using eviews as an analytical tool to test the hypothetical model. The research findings show that inflation and open unemployment rate have a positive and significant impact on income inequality. From the results of the determination test, this means that income inequality in Riau province can be explained by the inflation variable and the open unemployment rate with a value of 73.21%, while the remaining 26.79% is explained by variables outside the research model. Finally, based on these findings, we propose some promising research directions and implications for government policymakers to consider the level of stability of the inflation rate, and also create jobs so that the unemployment rate decreases so that income inequality also decreases.